Prevalence and Antibiotic Resistance Profile of Secondary Bacterial Pneumonia and Bloodstream Infection Among Hospitalized COVID-19 Patients and Their Relation to Procalcitonin - Azhin D. Aziz; Adel K. Khider (Polytechnic Journal)
Background and Objectives: in COVID-19 patients, secondary bacterial infections (SBIs) are a known complication of viral respiratory infections and are significantly associated with poorer outcomes.Our study aimed to determine the prevalence, clinical profile, antimicrobial resistance profile, and patient outcomes of secondary bacterial pneumonia and blood infections in COVID-19 hospitalized patients and their correlation with procalcitonin (PCT) levels.Method: During 7 months’ study, 260 clinical samples (blood and respiratory specimens) were collected from 130 hospitalized COVID-19 patients, of which 90 were from intensive care units (ICUs) and 40 from non-ICU departments, at six hospitals in Erbil city, Iraq. All samples were applied for bacterial identification via traditional method, Vitek-2 compact system, and molecular (PCR) detection. The antibiotic resistance profile was obtained via Vitek-2 compact system and the Standard International Kirby-Bauer disc diffusion method. Finally, the inflammatory biomarkers (PCT, C-reactive protein CRP, and WBC count) wereevaluated.Results: Among 130 patients, 64.16% were positive for SBIs, of which 86.9% from the ICU and 13.1% from the non-ICU department. The most prevalent isolates were gram-negative (77.7%) versus gram-positive (22.3%) bacteria. Klebsiella pneumoniae, Acinetobacter baumannii, and coagulase-negative staphylococci were the predominant isolates in both blood and respiratory specimen. There was an obvious relation between mortality rate and SBIs in the studied patients, which reached 81%. Most of the isolated bacteria, especially ICU isolates, were multidrug resistant. PCT increased in 79 (89.8%) of the patients with SBIs. The highest PCT level was found in patients with bloodstream infection.Conclusion: There is a high prevalence of bacterial superinfections in COVID-19 patients during hospitalization. Gram negative bacteria, especially Klebsiella pneumoniaeand Acinetobacter baumanniiwere the main bacteria, and the antimicrobial resistance rates against the major isolated bacteria were generally high. ThePCT level was positively associated with secondary bacterial infection and patient outcome.